Water policy debate in Australia: Understanding the tenets of stakeholders' social trust. (April 2017) - Wheeler, Sarah Ann; Hatton MacDonald, Darla; Boxall, Peter
Abstract: The increasing physical and economic scarcity of water due to increasing societal demands and climate change will require worldwide water policy reform. Water reform is an area of public policy fraught with polarised positions regarding community and environmental welfare. As opposition to water policy reform becomes entrenched, transaction costs increase. Nowhere is this more evident than the controversy surrounding, and irrigators' opposition to, the Murray-Darling Basin Plan in Australia. This study sought to understand irrigators' trust issues and why they feel the way they do towards water reform, though a best-worst survey methodology and regression analysis. The results suggest that irrigators believe they are shouldering a fair share of the water reform burden. Lack of trust in the national water agency and the federal government is associated with irrigator location, age and climate change disbelief. Findings support the recent push for more localised water decision-making to promote social trust.